Implementation of the Independent Curriculum through the Merdeka Mengajar Platform at the Early Childhood Education Level in West Sumbawa Regency, Indonesia - Ratna, R.; Khadafie, Muammar (Golden Ratio of Social Science and Education, 2025)
Implementing the Merdeka Curriculum at the Early Childhood Education (PAUD) level is a strategic step toward shaping Indonesia's golden generation from an early age. This curriculum emphasizes child-centered learning tailored to individual needs and interests while fostering positive character development through meaningful experiences. Sumbawa Barat Regency, one of the regions adopting the Merdeka Curriculum in PAUD institutions, demonstrates a strong commitment to supporting national educational transformation. The Merdeka Mengajar Platform is a digital tool to assist teachers in understanding, planning, and implementing learning activities aligned with the principles of Merdeka Curriculum. PAUD teachers can access teaching modules, self-paced training, inspirational videos, and diagnostic assessments to design contextual and engaging learning activities through this platform. It also supports continuous teacher competency development. In practice, PAUD teachers in Sumbawa Barat Regency have shown high enthusiasm for using the Merdeka Mengajar Platform. However, challenges such as limited digital infrastructure, technological literacy gaps, and the need for intensive mentoring remain obstacles to overcome. Sustained support from local governments and educational institutions is crucial to optimizing the platform's potential. This study highlights the positive impact of the Merdeka Curriculum and Merdeka Mengajar Platform on enhancing PAUD learning quality, though room for improvement exists. By strengthening teacher training and infrastructure, the platform can become a key driver of adaptive and relevant early childhood education transformation, keeping pace with modern advancements.